HUBUNGAN VOLUME, KECEPATAN DAN KEPADATAN DENGAN MODEL GREENSHIELDS, GREENBERG, DAN UNDERWOOD PADA RUAS JALAN LUAR KOTA KAWASAN GUNUNG GEURUTEE - Ari Juanda; Muhammad Isya; Noer Fadhly (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
In Indonesia, Karl-L Bang research in 1994 on the relationship between traffic parameters was included in the Indonesian Road Capacity Manual 1997. The research has undergone many changes between 1994 and 2018 in the growth of traffic that may affect traffic flow and volume, speed and density all urban roads, roads outside the city in an area, In Aceh studies have also been conducted into the relationship between traffic parameters on different roads. On this basis, it is very necessary to know the characteristics of traffic flows that occur on the Banda Aceh - Meulaboh section 65+450 is located in Aceh Jaya Regency, in the province of Aceh. Given that this road is located in an extremely mountainous area, where there are many very steep curves and ravines and rocks on the cliff side of the road. Analysis using models Greenshields, Greenberg, and Underwood. The results of the study show that the Greenshields model is the most satisfying compared to the Greenberg model and the Underwood model with a coefficient of determination (R2) greater than 0.88. The model is by the traffic conditions on the Outer City Road. Then the traffic flow obtained can not reach optimum conditions, namely in a stable traffic flow condition. The relationship between speed and density (S-D) with the model equation is S = 36,525 - 0,815 D; The volume-density (V-D) relationship with the model equation is V = 36,525 D - 0,815 D2; The relationship of volume - speed (V-S) with the model equation is V = 44,835 S - 1,228 S2